2017
DOI: 10.1016/j.ces.2016.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Breakage of fractal agglomerates

Abstract: (a) D f =2.13 (b) D f =2.33 (c) D f =2.55 (d) D f =2.80 Generalized correlation between the damage ratio (D m) and fractal dimension (D f)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 41 publications
(73 reference statements)
4
22
0
Order By: Relevance
“…Figure 5 gives the connection between fractal dimension and yield stress when the flocculation is carried out at different mixing rates. An apparent decrease in the fractal dimension is generated with the increase of the mixing, which is agreeable with that declared by Deng and Davè [37], who state that when aggregates are produced with a higher shear rate, they grow irregularly, resulting in lower fractal dimensions. On the other hand, more aggressive hydrodynamics deteriorates the structure of the aggregates, promoting the reduction of the fractal dimension.…”
Section: Analysis Of Yield Stresssupporting
confidence: 90%
See 1 more Smart Citation
“…Figure 5 gives the connection between fractal dimension and yield stress when the flocculation is carried out at different mixing rates. An apparent decrease in the fractal dimension is generated with the increase of the mixing, which is agreeable with that declared by Deng and Davè [37], who state that when aggregates are produced with a higher shear rate, they grow irregularly, resulting in lower fractal dimensions. On the other hand, more aggressive hydrodynamics deteriorates the structure of the aggregates, promoting the reduction of the fractal dimension.…”
Section: Analysis Of Yield Stresssupporting
confidence: 90%
“…At a fixed mixing rate, the yield stress presented a seemingly exponential increase over the fractal dimension. This agreement with the proposed by Deng and Davè [37], who established that a lower fractal dimension leads to a lower mechanical strength of the agglomerate, which was determined by the model proposed by Kendall and Stainton [38]. The authors considered the porosity, adhesion work and particle diameter.…”
Section: Analysis Of Yield Stresssupporting
confidence: 88%
“…This behavior may reflect the porosity of the aggregates that made up the sediment: The higher aggregation of particles at pH 5.7 was due to face-edge bonds and generated structures with lower porosity than particles dispersed at pH 7.3. Deng and Davè [39] found that when aggregates are produced at a higher rate, they grow irregularly, resulting in lower fractal dimensions. After the addition of the flocculant, there was a decline in the solid concentration, which was the result of the formation of large porous aggregates [40].…”
Section: Sediment Solid Concentrationmentioning
confidence: 99%
“…The formation of soot particles in diesel engines is affected by factors such as temperature, pressure, soot particle concentration, and oxidation rate [17]. According to the characteristics of free particles moving in a continuous medium state, it can be considered that the soot growth of a soot particle (condensation collision) has a distribution parameter equation of motion with boundary conditions as Eq.…”
Section: The Theory Of Controlmentioning
confidence: 99%